Identifying anemia determinant factors in adolescent girls to improve productivity: A systematic review - Ni Putu Wahyu Laksmi Natha Devi; Luh Seri Ani; Komang Ayu Kartikasari (Institute of Computer Science (IOCS), 2026)
Anemia has a negative impact on the productivity of adolescent girls. However, adolescents' understanding of risk factors for anemia is still limited. Therefore, a literature study was conducted to provide knowledge about the determinant factors of anemia for adolescent. The purpose of this literature review is to identify determinant factors for the incidence of anemia in adolescent girls. This study was systematically compiled based on a literature search using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) method. Data was collected from Google Scholar and PubMed electronic databases from May to June 2024. Articles are disaggregated based on inclusion and exclusion criteria. The criteria for journal inclusion are articles published in the 2019-2024 range, Indonesian and English language journals. The criteria for journal exclusion are incomplete journals. Two reviewers independently assessed the feasibility of the article using the Newcastle Ottawa scale guidelines. A total of 20 articles were considered feasible. Factors related to the incidence of anemia in adolescent girls include dietary patterns, body image, physical activity, nutritional status, iron consumption, disease history, menstruation, and adolescent girls' knowledge. The results of this study have implications for adolescents' understanding of preventable anemia risk factors. In addition, this research contributes to the improvement of adolescent productivity through an understanding of the determinants of anemia in adolescents. Therefore, it is recommended to further research is expected to evaluate effective models of anemia prevention for adolescents to increase adolescent productivity.